FINDINGS FROM “LEARNING AND TEACHING FOREIGN LANGUAGES IN LOWER SECONDARY SCHOOL”, (BUNJO 2012): IMPLICATIONS FOR THE EDUCATION OF TEACHERS OF ENGLISH. - Ellis, Melanie (Neofilolog, 2019)
This paper takes data from the first part of a longitudinal study, “Learning and Teaching Foreign Languages in lower secondary school”, conducted by the Educational Research Institute in Warsaw. The sample is large scale and representative at the level of school, which allows us to generalise to the general population with some degree of confidence. From the data several areas appear to give cause for concern. The first is organisation of work in class, where pair and group work were found to be rare. The focus of lessons would currently appear to more often emphasize grammar, vocabulary or receptive skills than productive skills. What is tested does not always seem to reflect what is taught, which suggests that assessment practices may not be fully informed. Motivating learners and engaging them in the lesson is also reported as a cause of dissatisfaction. Teachers were found to hold mixed views regarding the importance of independent learning, which suggests more emphasis needs to be placed on the understanding of learner autonomy. This paper discusses each of these areas in turn, with illustrations from the data, and makes suggestions for how teacher education could be enhanced.